Conducting Slug Tests in Mini‐Piezometers. Issue 2 (26th March 2015) - Fritz, Bradley G.; Mackley, Rob D.; Arntzen, Evan V.
Abstract: Slug tests performed using mini‐piezometers with internal diameters as small as 0.43 cm can provide a cost effective tool for hydraulic characterization. We evaluated the hydraulic properties of the apparatus in a laboratory environment and compared those results with field tests of mini‐piezometers installed into locations with varying hydraulic properties. Based on our evaluation, slug tests conducted in mini‐piezometers using the fabrication and installation approach described here are effective within formations where the hydraulic conductivity is less than 1 × 10 −3 cm/s. While these constraints limit the potential application of this method, the benefits to this approach are that the installation, measurement, and analysis is cost effective, and the installation can be completed in areas where other (larger diameter) methods might not be possible. Additionally, this methodology could be applied to existing mini‐piezometers previously installed for other purposes. Such analysis of existing installations could be beneficial in interpreting previously collected data (e.g., water‐quality data or hydraulic head data).